2000
DOI: 10.1034/j.1600-051x.2000.027008590.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subgingival scaling during supportive therapy

Abstract: These findings call into question the value of performing repeated subgingival scaling at 3-month intervals for patients with persistent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 28 publications
1
63
2
Order By: Relevance
“…Only one study (Jenkins et al 2000) compared directly both of the interventions of interest: supragingival prophylaxis and subgingival debridement. There was no reference to randomization of the patients who were recruited on the basis of having sites which did not respond to non‐surgical treatment comprising hygiene phase, scaling and root planing.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Only one study (Jenkins et al 2000) compared directly both of the interventions of interest: supragingival prophylaxis and subgingival debridement. There was no reference to randomization of the patients who were recruited on the basis of having sites which did not respond to non‐surgical treatment comprising hygiene phase, scaling and root planing.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Six studies compared PM delivered in both settings by splitting their cohorts into test and control groups to receive either specialist or PDC maintenance or PM that might be deemed similar to that delivered in PDC but which was delivered in a hospital environment (Nyman et al. , Jenkins et al …”
Section: Resultsmentioning
confidence: 99%
“…comparing values to pre‐APT levels, while Axelsson and Lindhe, Cortellini et al . and Jenkins et al . used the start of PM as their baselines.…”
Section: Resultsmentioning
confidence: 99%
“…1,2,3,4,5 However, during the past 20 years the subgingival scaling and root planing (SBG) has been associated to that control and this association (SPG+SBG) been recognized as the choice therapy during periodontal maintenance period (PMP). 6,7,8 Nevertheless, studies comparing this combination to other protocols were not available until recently when a clinical study 9 and two systematic reviews 10,11 suggested that the SPG biofilm control alone might be the choice during PMP. The authors showed no clinical outcomes benefits from the addition of the subgingival scaling (SPG + SBG).…”
Section: Introductionmentioning
confidence: 99%